Generation of expressed sequence tags (ESTs) database and isolation of alcohol dehydrogenase gene from young leaf samples of metroxylon sagu - Wee, Ching Ching. (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Alcoholic fermentattion in plants with reduction of acetaldehyde by alcohol dehydrogenase to produce energy is one of the metabolic pathways that enables plant to withstand stress. Sago plam is important to the state of Sarawak as one of the most important crops that bring huge revenue. It has the ability to withstand stress by growing well in waterlogged area. Shoots of sago palm in the early development stages has a high alcohol dehydrogenase gene expression. In this study, the gene expression in selected sago palm tissue was studied via the generation of expressed sequence tags of young leaves and isolation of full length adh cDNA from sago palm leaves using a combination of RACE and DNA walking method.